2018
DOI: 10.1039/c7cc09603h
|View full text |Cite
|
Sign up to set email alerts
|

The deformation of hydrogel microspheres at the air/water interface

Abstract: The deformation of soft hydrogel microspheres (microgels) adsorbed at the air/water interface was investigated for the first time using large poly(N-isopropyl acrylamide)-based microgels synthesized by a modified aqueous precipitation polymerization method. The deformation of the micron-sized soft microspheres could be visualized clearly and analyzed quantitatively at the air/water interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 45 publications
1
60
0
Order By: Relevance
“…There is ample experimental evidence (Geisel et al, 2015), (Minato et al, 2018, Zielinska et al, 2017, Zielinska et al, 2016) that microgels change their shape on adsorption, as well as simulations and theoretical models that describe this (Matsui et al, 2017), (Mourran et al, 2016), (Rumyantsev et al, 2016). Gelissen et al (Gelissen et al, 2016) have recently used in situ electron and super-resolved fluorescence microscopy techniques to visualize microgel internal structure during swelling and shrinkage.…”
Section: Deformation Of Microgels On Adsorptionmentioning
confidence: 99%
“…There is ample experimental evidence (Geisel et al, 2015), (Minato et al, 2018, Zielinska et al, 2017, Zielinska et al, 2016) that microgels change their shape on adsorption, as well as simulations and theoretical models that describe this (Matsui et al, 2017), (Mourran et al, 2016), (Rumyantsev et al, 2016). Gelissen et al (Gelissen et al, 2016) have recently used in situ electron and super-resolved fluorescence microscopy techniques to visualize microgel internal structure during swelling and shrinkage.…”
Section: Deformation Of Microgels On Adsorptionmentioning
confidence: 99%
“…Soft and surface‐active microgels adsorb and assemble spontaneously into monolayers at the air/water interface during the evaporation of water from dilute microgel dispersions. Soft microgels are highly deformed at the interfaces, before they pack hexagonally as the water evaporates . So far, the effects of the size, softness, and chemical composition of the microgels on the self‐organization process have been clarified, and fast fabrication methods to produce homogeneous microgel thin films have been developed .…”
Section: Figurementioning
confidence: 99%
“…On the other hand, for ESN‐N microgels, the high percentage of side‐to‐side blocks was maintained until complete drying ( T N =1.0), while the collapse of one‐dimensional assemblies was suppressed. The difference between ESN and ESN‐N is likely related to the softness of the ESN‐N microgels, whereby the highly deformed microgels that exist at the air/water interface lead to physical crosslinking of the surface polymer chains of neighboring microgels, similar to spherical microgels ,…”
Section: Figurementioning
confidence: 99%
“…So far, there have been many attempts to determine the accurate structure of pNIPAm‐based microgels. The structure of microgels has been mainly studied by scattering techniques, and imaging techniques including electron microscopy, fluorescence microscopy, atomic force microscopy (AFM), and super‐resolution microscopy . Most of these previous reports have concluded that pNIPAm‐based microgels prepared by precipitation polymerization exhibit an inhomogeneous structure of the core‐shell, where the polymer density of the core is higher than that of the shell, which originates from the difference in reactivity between NIPAm and BIS, that is, BIS is consumed faster than NIPAm .…”
Section: Figurementioning
confidence: 99%